Effect of community driven development project on local economic development in Tatkon township, Myanmar (FY2014-15 toFY2017-18) - Aung, Chan Nyein (Brac University, 2020)
This thesis is submitted in partial fulfillment of the requirements for the degree of Masters of Arts in Governance and Development, 2019.